SAT0342 Medical Adherence in Systemic Lupus Erythematosus – Results of the Lula-Study. (9th June 2015) - Chehab, G.; Sauer, G.M.; Richter, J.G.; Willers, R.; Fischer-Betz, R.; Winkler-Rohlfing, B.; Schneider, M.
Abstract : Background: Medical adherence is an important factor influencing therapeutic success. In the majority the lack of adherence remains unrecognised and/or is misinterpreted as non- respectively not adequate response. In Germany and several other countries medical costs are paid by a social health insurance system. Therefore, a lack of adherence with disposal of the unused drugs has a prejudicial effect on national economies. Objectives: Our objective was to investigate the frequency and influencing factors of low adherence in lupus patients in Germany. Methods: The LuLa-Study is a longitudinal cross-sectional survey of the German LE self-help community on a multitude of LE associated factors. It is being conducted annually by means of a self-reported questionnaire since 2001. Amongst others health-related quality of life is measured by the Short-Form-12 (SF-12) with its mental (MCS) and physical component summary (PCS), damage by using the "Brief Index of Lupus Damage" (BILD) and disease activity using the "Systemic Lupus Activity Questionnaire" (SLAQ). In 2012 we included additional questions concerning medical adherence (using the four item Morisky Medication Adherence Scale; MMAS-4) as well as satisfaction (numeric-rating-scale; 0-10) concerning their lupus medication (i. a. antimalarials, glucocorticoids, immunosuppressive agents). Results: In 2012 we received 579 questionnaires. The MMAS-4 was completed by 458 participants. 81 individuals did not currently take any lupus medication and in 40 cases the MMAS-4 was incomplete and therefore omitted. 62.7% showed a high, 32.5% a moderate and 4.8% a low adherence. Increasing age (p<0.001), lower physical functioning (p=0.030; SF-12 PCS), a better mental status (p=0.011; SF-12 MCS), and accumulated damage (p<0.001; BILD) went along with a better reported adherence. Other factors lacked significant differences between the low, medium and high adherence groups like disease activity, disease duration, number of lupus-specific drugs (range 1-5), intensity of lupus therapy (symptomatic, immunomodulatory, immunosuppressive), overall number of medications (including medication for comorbidities; range 1-12), and satisfaction with lupus specific drugs. In participants using azathioprine (n=96) or ciclosporine (n=15) a high adherence was reported more frequently (72% resp. 73%) than in users of mycophenolic acid (n=72; 61%), methotrexate (n=49; 57%) or antimalarials (n=252; 58%). Conclusions: Our reported adherence rates lie within the large range reported by the review of Costedoat-Chalumeau et al [1]. We disclose several aspects that need to be taken into account when evaluating and initiating a therapy in patients with lupus. Especially in younger patients and those with a worse mental status lower medical adherence should be considered. The choice of the medical agent might have an additional negative impact on patients' adherence. When initiating a therapy, potential obstacles should be addressed and discussed openly between patients and physicians. Thus, individual therapy planning may contribute to improved adherence and thus produce the best possible outcome. References: Adherence to treatment in systemic lupus erythematosus patients. Costedoat-Chalumeau et al. Best Pract Res Clin Rheumatol. 2013 Jun;27(3):329-40. Acknowledgements: The LuLa-study is supported by unrestricted grants from GlaxoSmithKline and UCB Pharma. Disclosure of Interest: None declared